ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LKPD DI PEMERINTAH KABUPATEN-KOTA DI PROVINSI PAPUA - Kogoya, Sria; Salle, Agustinus; Wijaya, Anthonius H.C (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The population in this study is regencies / cities in the Papua Province during the last three years,Â namely the 2015-2017 budget year, the data obtained is the LHP data that has been audited by the BPK. the sample used in all of these studies as many as 87 samples of local government financialÂ reports are all existing populations in the sample. The data analysis method used in this study usesÂ multiple linear regression analysis with the SPSS 16 program. This data is processed from June to theÂ beginning of the 2019 julli in Jayapura City, Papua Province. The results in this study indicate thatÂ the age of the Regional Government has a positive effect on the level of disclosure of regionalÂ financial statements (LKPD). and on the Local Government Size, the Number of OPD, and also theÂ Dependency Rate have a positive and insignificant effect on the level of disclosure while the audit findings themselves influence the level of disclosure of the LKPD.